Suggesting a sonographic index to measure ultrasound diaphragmatic MRR - Loizou, Christakis; Loizou, Christos P.; Matamis, Dimitrios; Soleimezi, E.; Minas, G.; Pattichis, Constantinos S. (My University, 2016)
Measurements of ultrasound diaphragmatic motion may provide important and essential information about diaphragmatic fatigue. In this work, we propose a semiautomated analysis system for measuring the diaphragmatic motion and estimation of the maximum relaxation rate (MRR) from ultrasound M-mode images of the diaphragmatic muscle. The proposed system was evaluated in three ultrasound images of the diaphragmatic muscle. The system is able to compute the diaphragmatic motion and extract quantitative parameters for systolic and diastolic times as well as the excursion, inspiration, cycle duration and the MRR. The proposed system was evaluated by a clinical expert. It is anticipated that it might be used in future in the clinical practice. Further validation and additional experimentation in a larger sample of images is required for further validating the system.
Keywords: Diaphragmatic motion analysis; Diaphragmatic muscle; Diaphragmatic ultrasound; Maximum relaxation rate (MRR)